Temperance Brennan : The Bone Code - Book 20 - Reichs, Kathy (New York : Scribner, 2021)
"#1 New York Times bestselling author Kathy Reichs returns with her twentieth gripping novel featuring forensic anthropologist Temperance Brennan, whose examinations, fifteen years apart, of unidentified bodies ignite a terrifying series of events. On the way to hurricane-ravaged Isle of Palms, a barrier island off the South Carolina coast, Tempe receives a call from the Charleston coroner. The storm has tossed ashore a medical waste container. Inside are two decomposed bodies wrapped in plastic sheeting and bound with electrical wire. Tempe recognizes many of the details as identical to those of an unsolved case she handled in Quebec years earlier. With a growing sense of foreboding, she travels to Montreal to gather evidence. Meanwhile, health authorities in South Carolina become increasingly alarmed as a human flesh-eating contagion spreads. So focused is Tempe on identifying the container victims that, initially, she doesn't register how their murders and the pestilence may be related. But she does recognize one unsettling fact. Someone is protecting a dark secret-and willing to do anything to keep it hidden. An absorbing look at the sinister uses to which genetics can be put, and featuring a cascade of ever-more-shocking revelations, The Bone Code is Temperance Brennan's most astonishing case yet-one that gives new meaning to today's headlines"--
Keywords: Mystery fiction